Pioneer burnout: Radical product innovation and firm capabilities - Christina Guenther (Max Planck Institute of Economics, 2009)
The question of whether and when to enter a newly emerging product market has been the focus of practitioners as well as researchers. This paper contributes to the literature by investigating the order of entry as well as pre-entry experiences with a population-based approach for the radically new product market of multifunctional machine tools for the case of Germany between 1949 and 2002. Estimation results show, that later entrants outperform pioneers. Moreover, it turns out that industry and technology specific capabilities do not increase survival chances. But when decomposing the known positive age effect on survival, we see that particularly dynamic capabilities, i.e. the competence to integrate additional business activities into the current product portfolio, significantly lower the risk of failure in the new product market.
Keywords: 330